The influence of the rheological parameters on the dispersion of the flexural waves in a viscoelastic bi-layered hollow cylinder - Kocal, Tarik; Akbarov, Surkay D. (TECHNO-PRESS, 2019)
The paper investigates the influence of the rheological parameters which characterize the creep time, the long-term values of the mechanical properties of viscoelastic materials and a form of the creep function around the initial state of a deformation of the materials of the hollow bi-layered cylinder on the dispersion of the flexural waves propagated in this cylinder. Constitutive relations for the cylinder's materials are given through the fractional exponential operators by Rabotnov. The dispersive attenuation case is considered and numerical results related to the dispersion curves are presented and discussed for the first and second modes under the first harmonic in the circumferential direction. According to these results, it is established that the viscosity of the materials of the constituents causes a decrease in the flexural wave propagation velocity in the bi-layered cylinder under consideration. At the same time, the character of the influence of the rheological parameters, as well as other problem parameters such as the thickness-radius ratio and the elastic modulus ratio of the layers' materials on the dispersion curves, are established.
Keywords: flexural waves; rheological materials; viscoelastic material; wave dispersion; fractional-exponential operator; bi-layered hollow cylinder; AXISYMMETRICAL LONGITUDINAL-WAVES; ELASTIC-WAVES; GUIDED-WAVES; PROPAGATION; ATTENUATION; SCATTERING; DEFECTS; SURFACE; CURVES; Engineering